The Relationship Between Environmental Sanitation and Clean Water with Stunting Incidence in Toddlers in Panteraja - Eja Sapriansyah; Basri Aramico; Eddy Azwar (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Stunting remains a serious health problem in Indonesia, especially in Aceh Province, with several areas such as Pidie Jaya Regency experiencing high stunting rates, namely 37.8%. This study aims to evaluate the relationship between environmental sanitation and clean water availability on stunting in toddlers aged 1-5 years in Panteraja District, Pidie Jaya Regency, in 2023. Objective: To determine whether there is a relationship between Environmental Sanitation and Clean Water and the incidence of Stunting in Toddlers in the Panteraja Health Center Work Area in Pidie Jaya in 2023. Method: The study used a 1:1 case control design with 60 stunted toddlers and 60 non-stunted toddlers, taking place from January 11-21. Data were collected through questionnaires and analyzed using the Chi-square test and Odds Ratio (OR) using SPSS. Result: Univariate analysis showed that the average age of toddler mothers was >35 years, with the last education of elementary school (22.5%), junior high school (45.8%), and high school (31.7%). The gender of toddlers consisted of females (58%) and males (41.7%), with stunting and non-stunting incidents of 50% each. Bivariate analysis showed that environmental sanitation (p-value = 0.000, OR = 3.19) and clean water (p-value = 0.000, OR = 2.66) both had a significant relationship and were risk factors for stunting. Conclusion: This research concludes that sanitation and clean water have a significant effect on stunting. Public education and the role of government are important to reduce the prevalence of stunting in children under five.